Factors Affecting Work Productivity among Employees in the Business Process Outsourcing (BPO) Industry - L. Malicay, Rosalyn; C Gano-an, Jonathan (International Research Journal of Business Studies, 2023)
Employee productivity is influenced by a variety of factors. Productivity is essential for increasing employees’ performance, which contributes to organizations’ success. This study examines how work environment, work load, and supervisor support influence workforce productivity. Although several previous studies have investigated the factors influencing productivity, this study concentrates on three particular areas: workload, supervisor support and work environment. The primary data was gathered from business process outsourcing (BPO) employees, and an adapted questionnaire was distributed. A total of 100 business process outsourcing employees in Davao City completed the survey. The findings showed that a safe working place, workload, and the support of supervisor influenced the productivity of BPO employees. A p-value of < 01 indicates an association between a safe work environment, workload, and supervisor support and employee productivity. These results conclude that work environment, workload and supervisor support are positively influential on employee productivity among the BPO employees who participated in this study.